Kangaroo Mother Care and Lullaby Music Intervention for Stabilizing Pulse Rate and Body Temperature in Low Birth Weight Infants - Yuliana, Dewi; Herliana, Lia; Rosuliana, Novi Enis; Mariani, Dini (Journal of Pubnursing Sciences, 2025)
Background: Low Birth Weight (LBW) infants are a vulnerable group who have a high risk of experiencing instability of vital signs due to the imperfection of organs in the baby's body, especially the thermoregulation system and circulatory system. This instability can trigger serious complications and increase neonatal morbidity and mortality rates. Efforts to stabilize physiologically are important steps that need to be taken. Aims: To determine the effect of the combination of kangaroo mother care (KMC) intervention and lullaby music on the stability of pulse rate and body temperature of LBW. Method: This study uses a quantitative method with a quasi-experimental research design with a pretest-posttest with control group approach. The population was 94 people in October-December 2024 in the perinatology room. The research sample was 26 people using purposive sampling. The measuring instruments used include an axillary thermometer, stethoscope, timer, sound level meter, and observation sheet. Results: The results of the study using the paired t-test showed an increase in the average pulse rate and body temperature in the intervention group with a p value of 0.000, the control group with a p value of 0.049, while the results of the independent t-test for pulse rate after intervention with a p value of 0.012 and body temperature with a p value of 0.022. Conclusion: The combination of KMC and lullaby music is more effective in increasing the stability of pulse rate and body temperature of LBW. This combination intervention can be applied by nurses as suportive therapeutic nursing care for LBW.